PSYCHOLOGICAL CHARACTERISTICS AS PREDICTORS OF STUDENTS9 ACADEMIC ACHIEVEMENT (Annual of the Faculty of Philosophy in Skopje, 2014)
The aim of the research presented in this article is to investigate which psychological characteristics are related to students ’ academic achievement, and to find out the relative share of intelligence, creativity and achievement motivation in academic achievement prediction. A total of 319 students, of which 143 from primary schools (Ml = 12.9 years) and 176 from high schools (M2 = 16.8years) participated in the study. Psychological characteristics are measured by appropriate tests while the academic achievement scores were obtained on the basis of the students' answers to a questionnaire prepared by the author of this study. The results show that the joint effect of the predictor variables: creativity, achievement motivation and general intellectual ability, explains 30% of the academic achievement variance regarding elementary school students, whereas 18.6% of the variance of high school students' academic achievement. The obtained data are discussed in relation with the findings of the relevant studies.
Keywords: ACADEMIC ACHIEVEMENT; INTELLIGENCE; CREATIVITY; ACHIEVEMENT MOTIVATION; STUDENTS